2012
DOI: 10.1002/jbio.201200123
|View full text |Cite
|
Sign up to set email alerts
|

Near‐infrared imaging of breast cancer using optical contrast agents

Abstract: Breast cancer is the most common malignancy in women worldwide and the second leading cause of cancer death. On the basis of three studies performed by our group, this article reviews the current status of optical breast imaging using extrinsic contrast agents. To date, only two contrast agents have been applied in human studies, indocyanine green (ICG) and omocianine. Both contrast media were used for absorption and fluorescence imaging. Generally speaking, malignant breast lesions exhibited higher absorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 111 publications
0
13
0
Order By: Relevance
“…Breast cancer is considered the most common malignancy affecting women in the world, accounting for 16% of all female cancers (WHO Global Burden of Disease, 2004), and it is the second leading cause of death [1]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breast cancer is considered the most common malignancy affecting women in the world, accounting for 16% of all female cancers (WHO Global Burden of Disease, 2004), and it is the second leading cause of death [1]. …”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer is the most common malignancy and the second leading cause of death in women [1,2]. The causes and pathogenesis of breast cancer are poorly understood [2].…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the absorption/excitation (peak ∼800 nm) and emission (peak ∼820 nm) wavelengths have low absorption in tissue, permitting highly sensitive detection. ICG is used routinely in the clinic for measurement of cardiac output, in hepatology for liver function evaluation, in opthalmology for choroidal angiography, and in neurology for cerebral artery infarction detection [135]. In plasma, rapid binding of ICG to macromolecules like lipoproteins and albumin makes ICG act as a blood-pooling agent.…”
Section: Exogenous Contrast Agentsmentioning
confidence: 99%
“…Omocyanine is an ICG derivative with a plasma half-life of approximately 15 hours in humans and with superior quantum efficiency compared to ICG (i.e., higher florescence). However, absorption and fluorescence measurements did not differentiate between benign and malignant tumors with this particular agent [135, 145]. …”
Section: Exogenous Contrast Agentsmentioning
confidence: 99%
“…As a consequence of i)–iv), fluorescence dynamics in humans have been studied only in body-parts. The dynamic absorption and fluorescence contrast of the unspecific blood-pool tracer indocyanine green (ICG) [7], [8] have been shown to detect signs of rheumatoid arthritis [9], hemodynamic changes in diabetic feet [10], sentinel lymph nodes and lymph drainage [11][15], and breast cancer [16][20]. Feasibility studies in the brain have demonstrated that even deep tissue can be targeted [21][24].…”
Section: Introductionmentioning
confidence: 99%